(untitled) (Journal of Partial Differential Equations, 2020)
In this paper we considered the semi-linear equation of mixed type of second kind, k(x, y)u_tt + u_xx + a(x, y)u_t + P(x, y)u_t + y(x, y)u - |u|^pu = f(z,y) For the above equation, we solved the modified Tricomi problem and have proved the existence and uniqueness of strong solution in H_1.